2021
DOI: 10.1016/j.ajem.2020.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-flow nasal cannula and noninvasive ventilation in patients with COVID-19: A multicenter observational study

Abstract: Background The use of high-flow nasal cannula (HFNC) and noninvasive ventilation (NIV) in patients with COVID-19 is debated. Methods This study was performed in four hospitals of China from January to March 2020. We retrospectively enrolled 23 and 13 COVID-19 patients who used HFNC and NIV as first-line therapy, respectively. Results Among the 23 patients who used HFNC as first-line therapy, 10 experienced HFNC failure and used NIV as rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 26 publications
5
71
0
4
Order By: Relevance
“…The average rates of endotracheal intubation with invasive mechanical ventilation for patients who received HFNCO and NIV were 10.8% and 11.5% respectively. Our results are in accordance with the results of another study [11] which showed an average rate of endotracheal intubation for COVID-19 patients treated with HFNCO of 17%, and 15% for those treated with NIV; the average duration of therapy in this study [11] was 5.1 days for HFNCO and 6.8 days for NIV [11].…”
Section: Discussionsupporting
confidence: 92%
“…The average rates of endotracheal intubation with invasive mechanical ventilation for patients who received HFNCO and NIV were 10.8% and 11.5% respectively. Our results are in accordance with the results of another study [11] which showed an average rate of endotracheal intubation for COVID-19 patients treated with HFNCO of 17%, and 15% for those treated with NIV; the average duration of therapy in this study [11] was 5.1 days for HFNCO and 6.8 days for NIV [11].…”
Section: Discussionsupporting
confidence: 92%
“…rr=respiratory rate, PeeP=positive end expiratory pressure, r/i=recruitment/inflation ratio, CoPD=chronic obstructive pulmonary disease, CHF=congestive heart failure, HFnC=high flow nasal cannula, Wob=work of breathing, P/F=Pao2/Fio2 ratio, MaP=mean arterial pressure, niv=non-invasive ventilation doi: 10.1136/bmj.n436 | BMJ 2021;372:n436 | the bmj series. [93][94][95][96][97][98][99][100][101][102] It attests to the feasibility of utilizing HFNC in this setting; however, firm conclusions regarding efficacy are difficult to draw because of the lack of control groups. Table 1 shows large case series in the English language and provides detailed patient information and outcomes.…”
Section: Respiratory Care For Severe Covid-19 Pneumoniamentioning
confidence: 99%
“…Evidence on the use of HFNC for covid-19 pneumonia consists of case reports and case series 93949596979899100101102. It attests to the feasibility of utilizing HFNC in this setting; however, firm conclusions regarding efficacy are difficult to draw because of the lack of control groups.…”
Section: Respiratory Care For Severe Covid-19 Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…HFNC can improve oxygenation and reduce the respiratory rate [ 22 , 23 ]. In an observational study with a small sample size of critically ill patients with COVID-19 who used HFNC and NIV as first-line therapy, the duration of HFNC + NIV, intubation rate, and mortality did not differ between two groups [ 24 ].…”
Section: Introductionmentioning
confidence: 99%